Proceedings of the 15th International Conference on Computer Systems and Technologies 2014
DOI: 10.1145/2659532.2659621
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the flexibility of automated concept map based knowledge assessment

Abstract: Concept maps are an educational tool that is used both for learning and knowledge assessment. Automated knowledge assessment has a limited ability to assess non-standard constructions. and current automated concept map-based knowledge assessment systems fail to recognise the fact that learner's chosen labels for conceptual relationships may differ from teacher's preferred labels and still be correct. This paper conceptually introduces several mechanisms for overcoming this drawback which distinguish real misco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Second, there is a seemingly endless number of measures that could be used to characterize networks at the level of individual elements, groups, or for the whole network. For instance, other studies have reported the "ruggedness" (i.e., number of components) (Strautmane, 2012), the number of paths (Ifenthaler, 2010), or custom measures (e.g., percentage of nodes with in-and out-degree larger than one in Plate ( 2010)). It was recently shown that many of these measures are related, hence using more measures does not necessarily yield more insight (Wang and Giabbanelli, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Second, there is a seemingly endless number of measures that could be used to characterize networks at the level of individual elements, groups, or for the whole network. For instance, other studies have reported the "ruggedness" (i.e., number of components) (Strautmane, 2012), the number of paths (Ifenthaler, 2010), or custom measures (e.g., percentage of nodes with in-and out-degree larger than one in Plate ( 2010)). It was recently shown that many of these measures are related, hence using more measures does not necessarily yield more insight (Wang and Giabbanelli, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Both of the above examples also demonstrate that, currently, concept map grading software is unable to detect when a learner's choice of words does not precisely match the expert's preferred term but are still valid and correct, or when the inverse relationship is presented (e.g., "cows eat grass" rather than "grass is eaten by cows"). This could be improved with the development and use of a catalogue of relationships possible in concept maps, allowing the recognition of relationship symmetry and transitivity (Strautmane, 2014), or the incorporation of online dictionary and thesaurus software that can recognise synonyms and misspellings (Luckie et al, 2011).…”
Section: Online Concept Maps For Assessment and Feedbackmentioning
confidence: 99%
“…Practically, they offered instructors the opportunity to better evaluate where students conceptualizations began and understand how students retained constructed knowledge over the course of the semester. For additional examples of how to use and assess concept maps, Strautmane (2012) provides an excellent overview.…”
Section: Implications Of Conceptual Change Learning In Leadership Edu...mentioning
confidence: 99%